Plantar fascitis: case report - Mateos Simón, Piedad (Revista Internacional de Ciencias Podológicas, 2007)
The plantar fascitis, is one gives the reasons of pain in the heel, being the plantar fascitis the expression of an intermediate degenerative tear, produced by the repeated traumatism or by the fatigue of the plantar fascia, accompanying in occasions of chronic inflammation and occasional fibrosis. The lens of this one article is to give to know this clinical entity that with so many frequency we are emphisizing the differential diagnosis of other entities that they can deal with a similar symptomatology, as well as his treatment.